PERFIL NUTRICIONAL DE CRIANÇAS MENORES DE CINCO ANOS QUE FREQUENTARAM UM BERÇÁRIO INSTITUCIONAL - Andressa Gomes Barros Felizola; Rita de Cássia Coelho de Almeida Akutsu; Amanda Branquinho Silva; Karin Eleonora de Oliveira Sávio (Universidade do Estado do Rio de Janeiro, 2015)
Aim: To assess the nutritional status of children under five years of age who have attended an institutional nursery in the Federal District, Brazil. Methods: The sample consisted of children who have attended the institutional nursery between March 2010 and December 2013. The children and their mothers' socioeconomic, environmental, demographic, anthropometric and biological data were analyzed and a Food Frequency Questionnaire was applied in order to assess the children's food intake. To assess the diet overall quality, a score based on the Recommended Foods Score was used. Results: The sample consisted of 26 mothers and 28 children. As for the mothers, 67.9% were aged 31 to 40 years; 67.9% had postgraduate degrees; 85.7% were earning over 10 Brazilian minimum wages; 75% were married; 85.7% were normal weight and 14.3% were overweight. As for the children, their mean age was 29.44 months (± 14.18); 67.9% were exclusively on breast-feeding up to 6 months and 50% were weaned between 12 and 15 months; 88.9% of the children were eutrophic and 11.1% were at an overweight risk; 28.6% presented consumption of sugars and sugary drinks above what was recommended; 32.2% presented consumption of fruit below what was recommended and 67.9% had vegetable consumption below the recommended by the Brazilian Society of Pediatrics; 10.7% often had meals watching television and 21.4% never had meals watching television. The diet average score was 23.25 ± 2.31 points out of a total of 28. Conclusion: Attending an institutional nursery can positively contribute to children's nutritional status and eating habits. DOI: http://dx.doi.org/10.12957/demetra.2015.14141